Cloud Computing Technology in the Development of Digital Libraries to Increase Literacy in Indonesia - Pallahidu, Lakuntara; Iqbal, Muhammad; Salas, Juan Anthonio (Indonesian Journal of Librarianship, 2023)
Problem Statement: Cloud computing has the potential to increase literacy in Indonesia by enabling wider and more efficient access to sources of information through the creation of digital libraries that can be accessed anywhere and anytime. Purpose: In this analysis we can understand how Indonesian digital libraries are doing right now and outlines the difficulties they confront in giving their users access to information and resources. Method: This research is a descriptive qualitative research. Researchers chose to use this method because this research focuses on complex social phenomena, namely increasing literacy through the use of digital libraries supported by cloud processing technology. Result: The advantages of cloud computing technology for digital libraries, such as improved accessibility, improved cooperation, and increased efficiency, are also covered in the article. Conclusion: At the article's suggestions are made for using and implementing cloud computing technologies to increase literacy rates in Indonesia. Keywords: Literacy; Digital Libraries; Cloud Computing